Anatomy of the Intermetatarsal Facets of the Fourth and Fifth Metatarsals. Issue 1 (4th February 2021) - Qatu, Mossub; Borrelli, George; Traynor, Christopher; Weistroffer, Joseph; Jastifer, James
Background: The intermetatarsal joint between the fourth and fifth metatarsals (4-5 IM) is important in defining fifth metatarsal fractures. The purpose of the current study was to quantify this joint in order to determine the mean cartilage area, the percentage of the articulation that is cartilage, and to give the clinician data to help understand the joint anatomy as it relates to fifth metatarsal fracture classification. Methods: Twenty cadaver 4-5 IM joints were dissected. Digital images were taken and the articular cartilage was quantified by calibrated digital imaging software. Results: For the lateral fourth proximal intermetatarsal articulation, the mean area of articulation was 188 ± 49 mm 2, with 49% of the area composed of articular cartilage. The shape of the articular cartilage had 3 variations: triangular, oval, and square. A triangular variant was the most common (80%, 16 of 20 specimens). For the medial fifth proximal intermetatarsal articulation, the mean area of articulation was 143 ± 30 mm 2, with 48% of the joint surface being composed of articular cartilage. The shape of the articular surface was oval or triangular. An oval variant was the most common (75%, 15 of 20 specimens). Conclusion: This study supports the notion that the 4-5 IM joint is not completely articular and has both fibrous and cartilaginous components. Clinical Relevance: The clinical significance of this study is that it quantifies the articular surface area and shape. This information may be useful in understanding fifth metatarsal fracture extension into the articular surface and to inform implant design and also help guide surgeons intraoperatively in order to minimize articular damage.